Ideas suicidas y efectos en la conducta en hombre adulto de 27 años perteneciente a la ciudad Babahoyo - Llerena Ponce, Eileen Odalis (2023)
The present case study was carried out in the city of Babahoyo, with the objective of identifying suicidal ideas and their repercussion on the behavior of a 27-year-old adult man, which was carried out with the application of each of the knowledge Acquired during the learning process, suicidal thoughts can arise due to many factors, but are usually determined by an underlying condition such as depression, which is reflected in symptoms such as sadness, crying, difficulty sleeping, loss of appetite, isolation. Suicidal behaviors can be prevented and it is important to spread the signs of this problem to the population so that they are detected in time. Therefore, this study for data collection used the open interview to obtain more relevant data on the subjectivity of the user, for the systematization of the information obtained, the clinical history was used, for the emotional assessment, the inventory was used. Beck II Depression Inventory to quantify the presence of depressive symptoms, and the Rossemberg Depression Inventory was used to assess self-esteem. The case was approached from the Cognitive Behavioral Therapy model with the application of several cognitive restructuring techniques resulting in the modification of negative thoughts that were causing significant discomfort, work was done in collaboration with the patient who had the predisposition to obtain positive thoughts, learn to express their feelings and perform more social activities thus improving their quality of life